1994
DOI: 10.1016/0014-5793(94)01283-0
|View full text |Cite
|
Sign up to set email alerts
|

Classical, novel and atypical isoforms of PKC stimulate ANF‐ and TRE/AP‐1‐regulated‐promoter activity in ventricular cardiomyocytes

Abstract: Cultured neonatal rat ventricular myocytes were co-transfected with expression plasmids encoding protein kinase C (PKC) isoforrns from each of the PKC subfamilies (classical PKC-a, novel PKC-.e or atypical PKC-0 together with an atria1 natriuretic factor (ANF) reporter plasmid. Each PKC had been rendered constitutively active by a single Ala+Glu mutation or a small deletion in the inhibitory pseudosubstrate site. cPKC-a, nPKC-& or aPKC-c expression plasmids each stimulated ANF-promoter activity and expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…PKC has been shown to increase atrial natriuretic factor in ventricular cardiomyocytes (69) and more recently to be involved in cardiac sarcomeric protein phosphorylation (70), which can be relevant during mechanical heart stress (71). Interestingly, PKC participates directly in the activation of MAPK and NFkB in several cell types (reviewed in Refs.…”
Section: Discussionmentioning
confidence: 99%
“…PKC has been shown to increase atrial natriuretic factor in ventricular cardiomyocytes (69) and more recently to be involved in cardiac sarcomeric protein phosphorylation (70), which can be relevant during mechanical heart stress (71). Interestingly, PKC participates directly in the activation of MAPK and NFkB in several cell types (reviewed in Refs.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings coincide with those of Kerkela et al (18), who reported that downregulation of PKC-␣ with antisense oligonucleotides did not block agonist-induced upregulation of ANF mRNA in NRVMs. Studies by Decock et al (11) using transient transfection methods to overexpress PKC isoenzymes in NRVMs showed that upregulation of ANF expression was greater in cardiomyocytes that express PKC-⑀ than PKC-␣. Similarly, Strait et al (31) revealed an upregulation of ANF expression in NRVMs that overexpress a constitutively active mutant of PKC-⑀.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,12,13,19,20 Unlike the in vivo situation, a low expression of ANF is present in nonstimulated cardiomyocytes, [12][13][14]19 which explains the small reduction by treatment with Ad5ANFPLas even in the absence of ET-1. In the presence of ET-1, however, a stronger reduction of PL protein was observed, consistent with the known ET-1 responsiveness of the ANF promoter.…”
Section: Discussionmentioning
confidence: 99%